2020
DOI: 10.1099/mic.0.000981
|View full text |Cite
|
Sign up to set email alerts
|

R-type bacteriocins of Xenorhabdus bovienii determine the outcome of interspecies competition in a natural host environment

Abstract: Xenorhabdus species are bacterial symbionts of Steinernema nematodes and pathogens of susceptible insects. Different species of Steinernema nematodes carrying specific species of Xenorhabdus can invade the same insect, thereby setting up competition for nutrients within the insect environment. While Xenorhabdus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…The Xenorhabdus specie s produce an arsenal of toxins and antimicrobials, including xenorhabdicin, which is a bacteriocin of the phage-tail type. 217 When nematodes compete within the insect, those carrying symbionts more successfully reproduce, presumably due to the inhibition of the symbiont competitors. Xenorhabdicin was shown to be required for Xenorhabdus to outcompete a Xenorhabdus strain sensitive to, but not producing xenorhabdicin in a natural host environment.…”
Section: Cross-talks In Holobionts: Rsps As Weaponsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Xenorhabdus specie s produce an arsenal of toxins and antimicrobials, including xenorhabdicin, which is a bacteriocin of the phage-tail type. 217 When nematodes compete within the insect, those carrying symbionts more successfully reproduce, presumably due to the inhibition of the symbiont competitors. Xenorhabdicin was shown to be required for Xenorhabdus to outcompete a Xenorhabdus strain sensitive to, but not producing xenorhabdicin in a natural host environment.…”
Section: Cross-talks In Holobionts: Rsps As Weaponsmentioning
confidence: 99%
“…Xenorhabdicin was shown to be required for Xenorhabdus to outcompete a Xenorhabdus strain sensitive to, but not producing xenorhabdicin in a natural host environment. 217 A symbiont-mediated trade-off in host fitness across competitive contexts was established, since the costs of bacteriocin production make inhibitory strains with lower fitness than non-inhibitory ones in the absence of competition. 218 These results are in line with the rock-paper-scissors theory that was first proposed in vitro and in vivo for colicins, the proteinaceous bacteriocins produced by Escherichia coli .…”
Section: Cross-talks In Holobionts: Rsps As Weaponsmentioning
confidence: 99%
“…10 years later in another experiment [ 97 ], using another X. bovienii strain, the natural symbiont of S. jollieti , (called Xb-Sj) was a very weak antibiotic producer. It possesses a P2-like phage tail gene cluster (xbp1), that encodes genes for xenorhabdicin production (Steven A. Forst, personal communication).…”
Section: Coevolution and Co-speciation Of Epn/epb Symbiotic Associationsmentioning
confidence: 99%
“…In that experiment, X. szentirmaii was extremely sensitive towards the purified X. bovienii xenorhabdicin, and it did not produce effective xenorhabdicin against the X. bovienii Xb-Sj strain, at least not in poor Grace’s medium [ 97 ]. However, it was demonstrated that X. szentirmaii produced high-level antibiotic activity, which killed X. bovienii in a complete rich medium [ 97 ]. When the two species were co-cultured in either of the two media, X. szentirmaii was the winner.…”
Section: Coevolution and Co-speciation Of Epn/epb Symbiotic Associationsmentioning
confidence: 99%
“…Xenocin, produced by X. nematophyla , is an RNase delivered through a type III secretion system and produced under iron deprivation conditions [ 155 , 156 ]. Xenorhabdicin, also the product of several Xenorhabdus species, is an R-type or phage tail-like bacteriocin that targets other Xenorhabdus and Photorhabdus species [ 157 , 158 , 159 ]. Together with xenocin they are proposed to inhibit competition from closely related species in the iron-deficient larval environment [ 156 ].…”
Section: Entomopathogenic Bacteriamentioning
confidence: 99%